Cost and benefit analysis for climate-smart agricultural (csa) practices in the coastal savannah agro-ecological zone (aez) of Ghana - Karanja Ng'ang'a, Stanley; Miller, Vail; Owuso Essegbey, George; Karbo, Naaminong; Ansah, V.; Nautsukpo, Delali; Kingsley, Sam; Girvetz, Evan Hartunian (United States Agency for International Development, 2017)
Most countries in sub-Saharan Africa (SSA), including Ghana, rely on agriculture for their income and food security. Any initiative that might help to sustain and improve productivity in agriculture would be a crucial step in improving people’s livelihoods. The adoption of climate-smart practices is a key step in reducing the threat to the sustainability of agricultural production in Ghana. Yet, despite the concern about the threat caused by climate variability and change, little empirical analysis has been carried out to date on how best to tackle it. However, recently many of the development and government programs are being designed in such a way that if adopted, can tackle the problems associated with climate variability and change. The majority of rural farmers have now adopted these practices. However, the cost effectiveness of adopting these practices – a key ingredient to the policy-making processes – is challenging. The results presented in this report attempt to bridge the knowledge gap between the cost and effectiveness, using ex-ante cost-benefit analysis to assess the cost effectiveness of some of the proposed climate-smart agricultural practices. This study examines the private and social benefits and the costs of selected climate-smart agricultural practices as a step towards understanding their private and potential social benefits and costs and their implication in terms of deterring their adoption from the farmers’ viewpoint and any potential social benefits, if adopted.